Learning Multimedia Based on RPG Maker MV Material for Circumference and Area of Flat Shapes for Elementary School Students - Dewi, Ni Luh Putu Jayanti; Sujana, I Wayan (Journal of Education Technology, 2021)
Based on the pre-research, it is known that the implementation of learning during the Covid-19 pandemic causes students to become bored quickly and online learning multimedia is not yet available. To overcome this, development research is carried out to produce designs and learn multimedia that are suitable for use after going through the material expert test, learning media experts test, learning design experts test, individual trials, and small group trials. This research develops circumference and area of flat shapes for fourth-grade elementary school students based on RPG Maker MV by using the Hannafin and Peck model. The types of data used are qualitative and quantitative, with data collection methods and instruments namely questionnaires. Data analysis methods and techniques used are descriptive qualitative and descriptive quantitative analysis. The results of this development research are: 1) The design of learning multimedia based on RPG Maker MV is made for elementary students using the Hannafin and Peck model, 2) Feasibility of learning multimedia based on RPG Maker MV for circumference and area of flat shapes in elementary school students which include: (a) Material expert test get a percentage of 90% with very good qualifications (very feasible), (b) Learning media expert test get a percentage of 96.7% with very good qualifications (very feasible), (c) Learning design expert test get a percentage of 95% with very good qualifications (very feasible), (d) The individual trials get a percentage of 96.7% with very good qualifications (very feasible), (e) The small group trial get a percentage of 95.6% with very good qualifications (very feasible). So it can be concluded that the resulting learning multimedia is very feasible to be used in the learning process.